Promoting Economic, Social, and Cultural Rights: Challenges and Opportunities in International Human Rights Law - Yoan Barbara Runtunuwu; Indra Tjahyadi (Eastasouth Institute, 2023)
This paper examines the barriers to and opportunities for advancing socioeconomic and cultural rights in Indonesia within the context of international human rights law. The research employs qualitative research methods, such as legal analysis, policy evaluation, and case studies, to thoroughly analyze the topic. Its findings underscore the complexities of realizing these rights in Indonesia and the need for targeted policies, collaboration among stakeholders, and participation in international human rights mechanisms. The research contributes to the existing knowledge of human rights in Indonesia. It provides policymakers and stakeholders with recommendations to protect and realize economic, social, and cultural liberties.